Combined versus Single Perforator Propeller Flaps for Reconstruction of Large Soft Tissue Defects: A Retrospective Clinical Study - Bigdeli, Amir K.; Didzun, Oliver; Thomas, Benjamin; Harhaus, Leila; Gazyakan, Emre; Horch, Raymund E.; Kneser, Ulrich (Journal of Personalized Medicine, 2022)
Sufficient wound closure of large soft tissue defects remains a challenge for reconstructive surgeons. We aimed to investigate whether combined perforator propeller flaps (PPFs) are suitable to expand reconstructive options. Patients undergoing PPF reconstruction surgery between 2008 and 2021 were screened and evaluated retrospectively. Of 86 identified patients, 69 patients received one perforator propeller flap, while 17 patients underwent combined PPF reconstruction with multiple flaps. We chose major complications as our primary outcome and defined those as complications that required additional surgery. Postoperatively, 27 patients (31.4%) suffered major complications. The propeller flap size, the type of intervention as well as the operation time were not associated with a higher risk of major complications. A defect size larger than 100 cm2, however, was identified as a significant risk factor for major complications among single PPFs but not among combined PPFs (OR: 2.82, 95% CI: 1.01−8.36; p = 0.05 vs. OR: 0.30, 95% CI: 0.02−3.37; p = 0.32). In conclusion, combined PPFs proved to be a reliable technique and should be preferred over single PPFs in the reconstruction of large soft tissue defects at the trunk and proximal lower extremity.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Combined perforator propeller flap; Microsurgery; Perforator flap; Perforator propeller flap; Propeller flap; Soft tissue reconstruction